Cultivo in vitro de tres clones de Ficus benjamina L. - Trujillo, R.=700 1 Daquinta, M.; Cobo, I.; Escalona, M.; Borroto, C.G.
(En, Es)
Ilus., 9 ref.
Keywords: FICUS BENJAMINA; CLONES; CULTIVO IN VITRO; CUBA